Efeito da adição de microrganismos (bioaumento) em uma estação de tratamento de efluentes por lodo ativado em uma indústria de papel e celulose - Lazzaretti, Eduardo [UNESP]; De Campos, Andréia Ferraz; Nogueira, Júlio César Batista (My University, 2001)
The objective of the present essay was to evaluate the effect, on a real scale, of the addition of microorganisms in a activated sludge wastewater treatment plant in a pulp and paper plant in the state of Paraná, Brazil. The powdered microorganism mix product, in pre-dosed, water-soluble plastic bags, were added according to the flow, organic loading and hydraulic retention time of the system. The percentage reduction in BOD and COD, the inflow rate, and the organic load (in tons per day of BOD and COD) were tracked at the entry and exit points. The results obtained showed a significant increase in the percentage reduction of BOD (an average of 15%) and COD (an average of 30%), even with an increase in the flow and organic loading coming into the system. This reduction corresponds, on average, to 1.4 tons per day less COD to the surface discharge system. According to these results, the addition of such microorganisms represents an attractive alternative for improving wastewater treatment system performance.
The effects of adding commercial microorganisms for bioaugmentation, in an activated sludge wastewater treatment plant of a major paper industry